2013
DOI: 10.1002/bdd.1843
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring and pharmacokinetic compartmental analysis of sulpiride double‐peak absorption profile after oral administration to human volunteers

Abstract: The developed analytical method was suitable for use in pharmacokinetic studies and therapeutic drug monitoring implementation. Sulpiride was well tolerated by the patients without any serious adverse events being observed. The double peaks in the serum concentration-time profiles could be due to differential rates of absorption along the gastrointestinal tract. The discontinuous absorption model with two sites of absorption was adequate to describe the double-peak of the sulpiride plasma profile. ClinicalTria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…After Powders 4 and 5 were administered by intragastric administration, notoginsenoside R 1 and ginsenosides Rg 1 and Rb 1 exhibited double peaks in the C-T gures (Powder 4 was more obvious), which were consistent with results previously reported [21,33]. This result could be due to differential rates of absorption along the gastrointestinal tract, and this prolonged residence time of the drug in the body could be bene cial to the maintenance of the drug effect, but the mechanisms of the double peaks remain to be determined [34,35]. The data suggested that the decrease in particle size can successfully improve the bioavailability within a range of 213.93 ~ 90.38 μm (Powders 1 ~ 4), and the result was not in agreement with the dissolution data (Figure 2a-d).…”
Section: In Vivo Studysupporting
confidence: 89%
“…After Powders 4 and 5 were administered by intragastric administration, notoginsenoside R 1 and ginsenosides Rg 1 and Rb 1 exhibited double peaks in the C-T gures (Powder 4 was more obvious), which were consistent with results previously reported [21,33]. This result could be due to differential rates of absorption along the gastrointestinal tract, and this prolonged residence time of the drug in the body could be bene cial to the maintenance of the drug effect, but the mechanisms of the double peaks remain to be determined [34,35]. The data suggested that the decrease in particle size can successfully improve the bioavailability within a range of 213.93 ~ 90.38 μm (Powders 1 ~ 4), and the result was not in agreement with the dissolution data (Figure 2a-d).…”
Section: In Vivo Studysupporting
confidence: 89%
“…The finding that the effects of methylphenidate, which blocks both dopamine and noradrenaline transporters [51,52], were not accompanied by significant effects of the selective D2-receptor antagonist sulpiride is surprising. First, previous research has established that the present dose of sulpiride is effective at approximately 2 hours after intake, indexed in terms of both sulpiride plasma concentrations [40,53] and behavioral effects on reversal learning [54]. Second, the exact same dose of sulpiride did have a significant effect in Westbrook et al [31], where the exact same study protocol was applied.…”
Section: Discussionmentioning
confidence: 93%
“…Aspartate amino transferase transient elevation was reported in one patient in the absorption of eltrombopag occurs along the gastrointestinal tract. 15,16 Enterohepatic circulation could also be a potential mechanism. 17 The plasma exposure (AUC 0-24 h and C max ) of hetrombopag in CITP patients increased greater than dose-proportional over the dose range of 2.5 to 7.5 mg/d, which was consistent with our previous observation in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%